"The Long and Winding Road": A Comparative Policy Analysis of Multilevel Judicial Implementation of Work‒Life Balance in Spain. Issue 1 (1st January 2019) - La Barbera, MariaCaterina; Lombardo, Emanuela
ABSTRACT: This article studies how processes of policy implementation and the impact of a multilevel European legal order shape social policies. By using an interdisciplinary approach to comparative policy analysis that investigates policy implementation through the critical study of judicial litigation, the article analyses the case of García Mateos on work‒life balance in its different stages before Spanish and supranational courts. It shows that the implementation of work‒life balance policy through litigation in Spain is a "long and winding road" paved with discursive and material opportunities and obstacles. While multiple pressures, actors, and framings at different governmental levels contributed to a favourable judicial decision on gender equality, norms about the gendered division of labour limited its transformative potential.